Lopian Boru Sinambela : gadis pejuang dari tanah Batak - Malau, Gens G.; Simanjuntak, Payaman J.; Sinambela, Boru Lapian (Jakarta : Diterbitkan oleh Yayasan "Taotoba Nusabudaya" bersama Partukkoan Dalihan Natolu, 1997)
Biography of Lopian Boru Sinambela, ca. 1890-1907, and her role against Dutch colonization in Tapanuli, Sumatera Utara Province.
Includes bibliographical references (p. 229).
Keywords: Batak (Indonesian people) -- History; Nationalists -- Indonesia -- Biography